Children's services in Spain: a study of the organisation and implementation of children's services in three regions in response to European recommendations. Issue 4 (19th December 2016) - Moreno, Almudena; Lara Montero, Alfonso
Abstract : Purpose: The purpose of this paper is to map the current organisation and implementation of children's services in three regions of Spain, to identify strengths and gaps and to suggest proposals for improvement in line with European recommendations. Design/methodology/approach: Spain features a decentralised approach when it comes to the organisation of children's services. This means that relevant themes for children's services refer to decentralised policies, which diverge within the regions in the country and therefore to illustrate this the authors focus on three specific regions. The study used an exploratory case study design and relied on qualitative methods, including the answers to open questionnaires provided by senior civil servants at key regional child welfare agencies, children's services directors and service providers. Findings: The main finding from the review of the legislation and the answers to the questionnaires is that public social services still follow an assistance logic rather than a social investment approach in regards to children's services. Although a significant development of laws and policies has taken place, ensuring the implementation, monitoring and evaluation of programmes and services for children remains a challenge. Research limitations/implications: The answers provided by the respondents may be subject to limitations imposed by the agencies for which they work. A general disadvantage of qualitative research is the use of subjective criteria to interpret the relevance of the results. The study was further challenged by differences across regions when it comes to their legal and policy frameworks, development of provisions and implementation and outcomes' evaluation. Practical implications: The findings could be used to assess the state of play in regards to children's services across the regions studied and beyond with a focus on children being placed at the centre of public services' intervention, using a comprehensive approach and promoting critical thinking and reflective practice. Social implications: The three selected case studies provide additional insight into policy and legal developments, implementation and evaluation of activities and efforts to improve policy and practice in children's services. Originality/value: This paper contributes to the evaluation of the current situation of children's services in Spain from a decentralised perspective with the aim to facilitate changes to improve planning, implementation and evaluation of children's services and secure better outcomes for children.